PENGARUH PROFITABILITAS, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Prasisca Riezky Maharani; Tri Kartika Pertiwi (Islamic University of Kalimantan MAB Banjarmasin, 2022)
This research aims to find out the effect of Profitability, Leverage, and Company Size on CSR Disclosure on companies listed in the kompas 100 Index in 2018-2019. The population in this study is a company listed in kompas100 index in 2018-2019 with purposive sampling techniques so that 140 companies are listed in the kompas100 index as samples. The type of data used is secondary data by using documentation methods as data collection. The data analysis techniques used are the outlier test, normality test, multicollinearity test, heteroskedasticity test, autocorrelation test, multiple linear regression analysis, hypothesis test. The results of this study showed that Profitability and Corporate Size did not contribute to CSR Disclosure, while Leverage contributed to CSR Disclosure in companies listed in kompas100 Index in 2018-2019. All these independent variables simultaneously contribute to CSR Disclosure.